Optimizing Official Government Websites for Information Dissemination: A Strategic Approach by the Department of Communication and Informatics of Solok City - Nirwana, Ida; Nasrah, Rasidah; Sari, Dila Kartiko (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the strategy for disseminating government websites by the Communication and Information Service in Solok City. The research type is a qualitative descriptive approach. The type of source used is primary data sources. This researcher used data collection techniques such as observation, interviews, and documentation. The informants used in the study were 13 people. The results show that the Communication and Information Service of Solok City utilizes its official website as the primary medium to convey information to the public quickly, transparently, and accessible at any time. This is in line with the spirit of public information transparency and the digitalization of government services. The information dissemination strategy implemented by the Communication and Information Service of Solok City through the official government website has been quite effective in conveying public information. However, it still needs to be strengthened in terms of human resources, collaboration between regional government agencies (OPD), and promotional efforts so that the website becomes the primary source of information accessed by the public. The public generally responded positively to the existence of the official website. However, the level of visits is still not optimal because some people are more active on social media than accessing the website.